Heat Strain pada Tenaga Kerja Bongkar Muat di Pelabuhan Kota Manado - Yekaterina Sipa Danduru; Oksfriani Jufri Sumampouw; Fima Lanra Fredrik G. Langi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Workers who are exposed to high temperatures while working indoors with hot environments or working outdoors with hot weather are conditions that have the potential to cause danger. One of the jobs that is directly exposed to the sun is the Loading and Unloading Workers (TKBM) at the port. Loading and unloading activities carried out under direct sunlight can increase the risk of heat strain. This study aims to determine the description of heat strain in TKBM at the Manado City Port. The study used a quantitative descriptive design with a cross-sectional approach. The sample in this study were all TKBM who were present and willing to be respondents with a total of 126 workers. Age data was obtained through interviews, pulse rate was measured using a pulse oximeter and heat strain was calculated using the Physiological Strain Index (PSI) which is based on body temperature and pulse rate measurements before and during work. Based on the results of the study, the average value of heat strain was 3.186 with a minimum value of 1.1 and a maximum of 5.4. Therefore, it can be concluded that TKBM at Manado City Port experienced an increase in heart rate and body temperature during loading and unloading activities, which reflects the presence of heat strain in most workers.